The Impact of Joint Family System on Women Autonomy: A Phenomenological Exploration - Haji Ur Rahman; Shahid Khan; Fakhr Ud Din; Shakeel Ahmad (Indus Journal of Social Sciences, 2025)
This study explores the impact of the joint family system on women's autonomy in the Hazara Division of Pakistan using qualitative methods and a phenomenological research design. Through purposive sampling, in-depth interviews were conducted with women experiencing the constraints of this system. Findings reveal that patriarchal norms significantly restrict women’s decision-making power, financial independence, mobility, and social participation. Senior male family members predominantly control household decisions, limiting women's influence over critical matters such as education, employment, and financial management. Economic dependence further diminishes autonomy, as many women are discouraged from working or lack control over their earnings. Additionally, mobility restrictions, often justified by family honor, curtail their independence. Despite these challenges, some women resist by pursuing education and employment, facing resistance from elder family members. The study recommends legal reforms, awareness campaigns, and community engagement initiatives to challenge restrictive norms and promote gender equality. Encouraging women's education and economic participation is crucial for their empowerment and broader social progress.